Mucilaginibacter sp. K Improves Growth and Induces Salt Tolerance in Nonhost Plants via Multilevel Mechanisms - Fan, Di; Smith, Donald L. (Frontiers in Plant Science, 2022)
Soil salinity negatively modulates plant growth and development, contributing to severe decreases in the growth and production of crops. Mucilaginibacter sp. K is a root endophytic bacterium that was previously reported by our laboratory to stimulate growth and confer salt tolerance in Arabidopsis (Arabidopsis thaliana). The main purpose of the present study is to elucidate the physiological and molecular machinery responsible for the prospective salt tolerance as imparted by Mucilaginibacter sp. K. We first report that auxin, gibberellin, and MPK6 signalings were required for strain K-induced growth promotion and salt tolerance in Arabidopsis. Then this strain was assessed as a remediation strategy to improve maize performance under salinity stress. Under normal growth conditions, the seed vigor index, nitrogen content, and plant growth were significantly improved in maize. After NaCl exposure, strain K significantly promoted the growth of maize seedlings, ameliorated decline in chlorophyll content and reduced accretion of MDA and ROS compared with the control. The possible mechanisms involved in salt resistance in maize could be the improved activities of SOD and POD (antioxidative system) and SPS (sucrose biosynthesis), upregulated content of total soluble sugar and ABA, and reduced Na+ accumulation. These physiological changes were then confirmed by induced gene expression for ion transportation, photosynthesis, ABA biosynthesis, and carbon metabolism. In summary, these results suggest that strain K promotes plant growth through increases in photosynthesis and auxin- and MPK6-dependent pathways; it also bestows salt resistance on plants through protection against oxidative toxicity, Na+ imbalance, and osmotic stress, along with the activation of auxin-, gibberellin-, and MPK6-dependent signaling pathways. This is the first detailed report of maize growth promotion by a Mucilaginibacter sp. strain from wild plant. This strain could be used as a favorable biofertilizer and a salinity stress alleviator for maize, with further ascertainment as to its reliability of performance under field conditions and in the presence of salt stress.